Disclosing the sacred in technological practices for sustainability - Hohenthal, Johanna; Ruuska, Toni Pekka Kalevi (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
Owing to the claimed loss of meaning in modern societies, this article investigates how the experience of the sacred is disclosed in technological practices. The experience of the sacred is studied through four framings that approach the sacred as (i) extreme im/purity or sublimity, (ii) a religious framework, (iii) a sense of connection, and (iv) a cognitive experience related to skills. Sacred experiences may emerge in all technological practices, but their meaning is implied to be of a particularly fleeting kind in highly technological practices – measured by their increase in matter-energy throughput – and prone to cause the experience of alienation. Sacred experience in less technological practices is consequently proposed to hold the potential to offer a more sustained experience of meaning. However, the proper kinds of skills are essential to reach experiences of the sacred that may serve to restore life and its purpose. Peer reviewed